THE CONTRIBUTION OF GROUP LEARNING FOR STUDENTS’ AUTONOMY AT ENGLISH EDUCATION DEPARTMENT OF UMY - Ibnu Muslim Putra Darmawan (PBI 15 UMY 049, 2015)
*49 Some students of English Education Department of UMY who do not understand or feel unclear about the explanation, they will usually ask their friends who know about it better rather than they put their hand up and ask the lecturer directly. Group learning can be an alternative method to solve the problems for the students by working and learning collaboratively. Also, they can possibly exercise their autonomy in learning from friend’s feedback. Therefore, the researcher was interested in conducting the research that focuses on discovering and describing contribution of group learning that they have experienced in the classroom for their autonomy in English learning at English Education Department of UMY. There were two research questions presented in this study: (1) how is group learning implemented at English Education Department of UMY? (2) What is the contribution of group learning for students’ autonomy at English Education Department of UMY? This research used a qualitative research design. To answer those two research questions, the researcher conducted an observation in class A batch 2013 in the subject matter of Capita Selecta on Grammar 4 in order to observe the implementation of group learning in the classroom. In addition, the researcher also conducted an interview with two participants and also focus group discussion with four students which those students were from the observed class because the researcher wanted to get richer data from the students. The data collected were then transcribed, categorized and analysed by using software of Weft Qualitative Data Analysis (WQDA). The result of the observation, interview and focus group discussion showed that there are four phases in the implementation of the group learning at English Education Department of UMY. Those four phases are (1) Group Forming, (2) Task Distribution, (3) Group Discussion and(4) Presentation. Subsequently, in the implementation of group learning, there vii are some contributions for students’ autonomy which are described into the characteristics of autonomous learner that dominantly appear in some particular phases although these characteristics can come out less dominantly all in phases. In phase one namely Group Forming, there was not dominant characteristic appeared because this phase ran briefly. In phase of Task Distribution, the students showed their learning awareness and selfmanagement dominantly. Furthermore, learning awareness, self-management, and learning motivation aroused in phase of Group Discussion and at this phase also, they knew proper learning resources for them selves. Lastly, learning motivation, self-management and learning awareness also emerged in phase of Presentation.